Catalytic interplay of metal ions (Cu2+, Ni2+, and Fe2+) in MFe2O4 inverse spinel catalysts for enhancing the activity and selectivity during selective transfer hydrogenation of furfural into 2-methylfuran. Issue 15 (27th June 2022) - More, Ganesh Sunil; Shivhare, Atal; Kaur, Surinder Pal; Dhilip Kumar, T. J.; Srivastava, Rajendra
Abstract : The substitution of Fe 2+ from the octahedral sites of the Fe3 O4 inverse spinel with Cu 2+ and Ni 2+ ions can be an effective strategy to synthesize cost-effective mixed metal oxide catalysts for the selective CTH of biomass-derived FUR to 2-MF. Abstract : 2-Methylfuran obtained via the hydrogenation of furfural is an important biomass-derived liquid fuel. However, the large-scale production of 2-methylfuran from furfural requires cost-effective, active, and selective heterogeneous catalysts. Herein, we have performed experimental and DFT investigations on MFe2 O4 (M = Cu 2+, Ni 2+, and Fe 2+ ) inverse spinel catalysts to selectively hydrogenate furfural into 2-methylfuran via transfer hydrogenation, and to determine the nature of active sites. CuFe2 O4 afforded 99.4% furfural conversion and 97.6% 2-methylfuran selectivity at 200 °C in 1.5 h. In contrast, NiFe2 O4 and Fe3 O4 catalysts afforded furfuryl alcohol as a major product. The comprehensive characterization of the catalysts revealed that the acidity of these inverse spinel catalysts originates from the Lewis acid sites. Further, the strength of Lewis acid sites and the associated catalytic activity trend directly correlate with the binding energy of Fe n + ions in MFe2 O4 catalysts. DFT calculations revealed the energetically favorable interactions of furfural and furfural alcohol with the Fe 3+ sites of Fe3 O4 and Fe sites (most likely Fe 3+ ) of CuFe2 O4 and NiFe2 O4 catalysts, whereas Cu 2+ and Ni 2+ sites present in CuFe2 O4 and NiFe2 O4 catalysts have stronger interactions with the isopropanol molecule. Hence, it is proposed that the Fe 3+ sites present in CuFe2 O4 are the active Lewis acid centers to selectively convert furfural into 2-methylfuran via transfer hydrogenation. Literature reports on the metal oxide catalyzed transfer hydrogenation of furfural into 2-methylfuran are rare. The present findings on the elucidation of the active sites of cost-effective, recyclable mixed metal oxide catalysts for the selective transfer hydrogenation of furfural into 2-methylfuran using isopropanol are attractive from the green chemistry perspective, and therefore extremely important for the academic catalysis community and to industrialists.